The status quo bias of bond market analysts - Zulia Gubaydullina; Oliver Hein; Markus Spiwoks (Journal of Applied Finance & Banking, 2011)
Status quo bias is a systematic cognitive error which makes it difficult for individuals to make decisions independently of the currently dominant situation. This study pursues the question of whether bond market analysts are affected by status quo bias. We evaluated interest rate forecast series from twelve industrial nations. This revealed that, on average, forecasts were much too close to the status quo - the current interest rate at the time when the forecast was made. With the aid of various analytical procedures it can be shown that the actual extent of interest rate changes is systematically and significantly underestimated.
Keywords: D03; G17; G12; 330; behavioral finance; status quo bias; bond market analysts; interest rate forecasts